Knockdown of miR-92a suppresses the stemness of colorectal cancer cells via mediating SOCS3. Issue 3 (1st March 2022) - Li, Lifa; Zhang, Jingxiao; Peng, Hong; Jiang, Xianhong; Liu, Zuoliang; Tian, Hongpeng; Hou, Songlin; Xie, Xingjiang; Peng, Qiang; Zhou, Tong
ABSTRACT: MiRNAs (microRNAs) participate in colorectal cancer (CRC) progression and act as potential biomarkers for CRC prognosis. In this study, we investigated the mechanisms of microRNA-92a (miR-92a) in CRC. Expressions of miR-92a and SOCS3 (Suppressor Of Cytokine Signaling 3) were investigated by qRT-PCR in CRC cell lines and 30 cases of CRC. The self-renewal capacity and proliferation of CRC stem cells were estimated by the sphere formation assay, EdU staining, and Flow cytometry analysis. Moreover, the interplay between miR-92a and SOCS3 in CRC cells was validated by luciferase reporter experiments. MiR-92a was found to be remarkably increased while SOCS3 was significantly downregulated in CRC tissues. Inhibition of miR-92a or SOCS3 attenuated the sphere formation capacity, decreased expressions of stemness-related proteins, and inhibited the proliferation of cancer stem-like cells. Knockdown of SOCS3 reversed the repressive impacts of miR-92a inhibitors on self-renewal and growth of CRC cancer stem cells. This study suggested that miR-92a functions as an oncogene of CRC through mediating the stemness of colorectal cancer cells by directly binding and repressing SOCS3. Abbreviations: CRC, cancer cell; CSCs, cancer stem cells; SOCS3, suppressor of cytokine signaling 3.